CORRELATION OF ABILITY OPINION SUGGESTED ABOUT RIGHT AND DUTY OF STUDENT IN THE SCHOOL WITH VIOLATION OF A RULE IN JUNIOR HIGHT SCHOOL 20 BANDAR LAMPUNG ON 2012/2013 - novita hariyani; Adelina Hasyim; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The aims of this research was to explain the correlation of ability opinion suggested about right and duty of student in the school with violation of a rule in Junior hight School 20 Bandar Lampung on 2012/2013. Method used correlational research. Sample was 21 persons. Data analyses used Chi Quadrate. Research result showed that: (1) correlation of ability opinion suggested about right and duty of student in the school (X) dominant on able enough category or 66,67%, (2) violation of a rule (Y) dominant on light category or 47,62%, (3) research result showed that there was positive, significant correlation and high bounded between correlation of ability opinion suggested about right and duty of student in the school with violation of a rule it means that if ability opinion suggested about right and duty of student in the school was more able, so violation of a rule of student was light.  Key Words: Opinion Suggested, Right and Duty of Student, Violation of A Rule